Determining Validity and Reliability of an In-Field Performance Analysis System for Swimming - Born, Dennis-Peter; Polach, Marek; Staunton, Craig (Sensors (Basel, Switzerland), 2024)
To permit the collection of quantitative data on start, turn and clean swimming performances in any swimming pool, the aims of the present study were to (1) validate a mobile in-field performance analysis system (PAS) against the Kistler starting block equipped with force plates and synchronized to a 2D camera system (KiSwim, Kistler, Winterthur, Switzerland), (2) assess the PAS's interrater reliability and (3) provide percentiles as reference values for elite junior and adult swimmers. Members of the Swiss junior and adult national swimming teams including medalists at Olympic Games, World and European Championships volunteered for the present study (n = 47; age: 17 ± 4 [range: 13-29] years; World Aquatics Points: 747 ± 100 [range: 527-994]). All start and turn trials were video-recorded and analyzed using two methods: PAS and KiSwim. The PAS involves one fixed view camera recording overwater start footage and a sport action camera that is moved underwater along the side of the pool perpendicular to the swimming lane on a 1.55 m long monostand. From a total of 25 parameters determined with the PAS, 16 are also measurable with the KiSwim, of which 7 parameters showed satisfactory validity (r = 0.95-1.00, p < 0.001, %-difference < 1%). Interrater reliability was determined for all 25 parameters of the PAS and reliability was accepted for 21 of those start, turn and swimming parameters (ICC = 0.78-1.00). The percentiles for all valid and reliable parameters provide reference values for assessment of start, turn and swimming performance for junior and adult national team swimmers. The in-field PAS provides a mobile method to assess start, turn and clean swimming performance with high validity and reliability. The analysis template and manual included in the present article aid the practical application of the PAS in research and development projects as well as academic works.
Keywords: Reproducibility of Results; reprodukovatelnost výsledků; mladiství; competitive swimming; youth; mužské pohlaví; plavání; Adult; mladý dospělý; elite athlete; Young Adult; ženské pohlaví; Humans; Swimming; junior; Video Recording; sportovní výkon; Athletic Performance; dospělí; Female; Adolescent; lidé; Male; audiovizuální záznam